Antioxidant and DNA damage protecting activities of Eulophia nuda Lindl. - Kumar, Vinay; Lemos, Melissa; Sharma, Mansi; Shriram, Varsha (Free Radicals and Antioxidants)
Introduction: In recent years, natural antioxidants have seen an unprecedented importance and demand in bio-pharmaceuticals, nutraceuticals besides their use as food additives. Antioxidants act as potential prophylactic and therapeutic agents against various diseases caused by free-radicals. Plants offer tremendous source of antioxidants and are therefore being evaluated for their potentials. Eulophia nuda is an important medicinal plant used by local healers in India; however its antioxidant properties have not yet been investigated. Methods: Aqueous (AqE), methanol (ME), aqueousemethanol (AqME) and acetone (AE) extracts of shade dried tubers were obtained and were concentrated in vacuo. Total phenols, flavonoids, ascorbic acid and carotenoids were estimated from all extracts using standard methods. Antioxidant activities of extracts were determined by total antioxidant activity, FRAP, ABTS, DPPH, and OH radical scavenging assays besides lipid peroxidation inhibition. Extracts were evaluated for protection of Fenton’s reagent induced DNA damage. Results: The results confirmed the plant as a rich source of phenols, flavonoids, vitamin C and carotenoids. Among four extracts, AqME showed highest antioxidant activities as evidenced by maximum scavenging of ABTS (98%), DPPH (87%), and OH radicals (99%) at 1 mg ml1 concentration and showed maximal inhibition of lipid peroxidation. All extracts protected the DNA from hydroxyl-radical-induced damage. Again, AqME was proved to be best in providing protection to DNA against damage caused by free- radicals. Conclusion: The results provides scientific basis for its traditional usage as natural antioxidant and phyto- therapeutic agent. The plant possesses high amount of phenolic compounds and showed a broad- spectrum antioxidant properties including DNA protection.
Keywords: Antioxidants; DNA damage protection; Fenton’s reagent; Lipid-peroxidation; Reactive oxygen species